Senior cycle review: Analysis of discussions in schools on the purpose of senior cycle education in Ireland - Joanne Banks; Selina McCoy; Emer Smyth (The Economic and Social Research Institute (ESRI), 2018)
This report is intended to inform the National Council for Curriculum and Assessment (NCCA) review of senior cycle and draws on the first cycle of the consultation process with 41 schools with different profiles and characteristics. The first cycle of the process has looked at teacher, parent and student perspectives on the purpose of senior cycle. The report outlines their perceptions of the benefits and challenges of the current senior cycle and their views on how senior cycle could be changed to address these challenges and to foster greater inclusion.
Keywords: 330